Pengaruh Ukuran Perusahaan, Profitabilitas Dan Kebijakan Deviden Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2017 – 2022 - Ramayana, Riski; Arseto, Dedy Dwi; Hulu, Fonaha (Accounting Progress, 2024)
This research aims to determine the influence of company size, profitability and dividend policy on company value in manufacturing companies listed on the Indonesian Stock Exchange for the period 2017 - 2022. The research method used is a quantitative method using SPSS version 25.00. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis tests, namely T test and F test. The results of SPSS in this research are that the Company Size variable has no effect on Company Value, The Profitability variable influences Company Value, the Dividend Policy variable influences Company Value, then Company Size, Profitability and Dividend Policy simultaneously influence Company Value.